Optimizing Pharmacotherapeutic Rationality and Pharmacy Practice: Strategies to Improve Clinical Outcomes and Patient Safety - Agung Budi Wicaksono (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aimed to optimize the rationality of pharmacotherapy, improve clinical outcomes, and ensure patient safety in healthcare services. A systematic review with thematic analysis was conducted on 25 scientific articles published between 2021 and 2026 and retrieved from PubMed, ScienceDirect, and Google Scholar. The selected articles were analyzed to identify the determinants of irrational drug use and strategies for improving pharmacotherapy quality. The findings revealed that irrational drug use is influenced by individual clinical factors and systemic healthcare barriers. Four major strategies were identified: strengthening patient-centered pharmaceutical care, implementing intelligent digital systems, enhancing interprofessional collaboration, and developing innovative drug dosage forms. In conclusion, the integrated implementation of these strategies has the potential to reduce medication errors, lower healthcare costs, improve therapeutic effectiveness, and enhance patients’ quality of life in a sustainable manner.